Work-related Post-traumatic Stress Symptoms in Obstetricians and Gynaecologists: Findings From INDIGO, a Mixed-methods Study With a Cross-sectional Survey and In-depth Interviews. Issue 1 (24th March 2021) - Slade, P.; Balling, K.; Sheen, K.; Goodfellow, L.; Rymer, J.; Spiby, H.; Weeks, A.
Abstract : ( BJOG . 2020;127:600–608) The impact of adverse mental health has been recognized as a major contributing factor in decreasing an individual's productivity and career satisfaction across both working class and professional individuals. Physicians are not exempt from this phenomenon and, in fact, are often at high risk of experiencing work-related posttraumatic stress disorder (PTSD) due to the not uncommon situation of exposure to trauma as a consequence of death or serious injury in their patients. To date, there has only been one study specific to obstetricians looking at the prevalence of PTSD that came out of the Netherlands. This study aimed to evaluate the prevalence and predictors of PTSD in physicians as well as the impact such has on both professional and personal functions.